Urgensi Penerapan Doktrin Business Judgment Rule terhadap Direksi BUMN dalam Perkara Tindak Pidana Korupsi - Hayyi, Muhammad Akram Syarif; Karim, Muhammad Said; Ilmar, Aminuddin (Universitas Negeri Malang, 2021)
The objective of this study was to hold directors accountable for company losses, the existence of business judgment rule in positive law, and the application of Business Judgment Rule as Legal Protection of the Board of Directors in Corruption Cases. The data obtained was presented analytically descriptively where the facts were described and later analyzed based on the laws and rules applicable in Indonesia as well as the theories. The accountability of the directors of State-Owned Enterprises for the company’s losses could be classified as acts that harm the state’s finances that include administrative, civil, and criminal responsibilities. The existence of business judgment rule doctrine in positive law had been regulated in Article 97 paragraph (5) of Law Number 40 of 2007 concerning Limited Liability Companies but had not been regulated technically related to the procedures for its application. The application of the business judgment rule doctrine as the protection of directors of State-Owned Enterprises in corruption cases should be used as material for consideration related to the removal of the defendant’s fault.